Who are we? : the challenges to America's national identity - Huntington, Samuel P. (New York : Simon & Schuster, 2004)
"America was founded by British settlers who brought with them a distinct culture including the English language, Protestant values, individualism, religious commitment, and respect for law. The waves of immigrants that later came to the United States gradually accepted these values and assimilated into America's Anglo-Protestant culture. More recently, however, national identity has been eroded by the problems of assimilating massive numbers of primarily Hispanic immigrants, bilingualism, multiculturalism, the devaluation of citizenship, and the "denationalization" of American elites." "September 11 brought a revival of American patriotism and a renewal of American identity. But already there are signs that this revival is fading, even though in the post-September 11 world, Americans face unprecedented challenges to our security."--BOOK JACKET.
Ch. 1. The crisis of national identity -- Ch. 2. Identities : national and other -- Ch. 3. Components of American identity -- Ch. 4. Anglo-Protestant culture -- Ch. 5. Religion and Christianity -- Ch. 6. Emergence, triumph, erosion -- Ch. 7. Deconstructing America : the rise of subnational identities -- Ch. 8. Assimilation, converts, ampersands, and the erosion of citizenship -- Ch. 9. Mexican immigration and Hispanization -- Ch. 10. Merging America with the world -- Ch. 11. Fault lines old and new -- Ch. 12. Twenty-first century America : vulnerability, religion, and national identity.
Includes bibliographical references (p. 367-410) and index.
Keywords: National characteristics, American; United States -- Civilization -- 1970-